Effects of Metal Ions on Laccase Activity - Wang, Xiwen; Hu, Jian; Liang, Yun; Zhan, Huaiyu (Asian Journal of Chemistry, 2011)
The effects of five metal ions (Fe2+, Ca2+, Mg2+, Mn2+, Cu2+) on 2,2'-azino-di(3-ethylbenzthiazoline- 6-sulfonic acid) (ABTS) oxidation catalyzed by laccase were studied by spectrophotometer. The results show that Fe2+ ion has obvious effect on the activity and the nature of inhibition is competitive type. It is found that the inhibition is realized through the reduction of 2,2'-azinodi( 3-ethylbenzthiazoline-6-sulfonic acid) by Fe2+ ion. Other metal ions have slight influence on laccase activity.